Estrogen activates Alzheimer's disease genes - Abhirami Ratnakumar; Samuel E. Zimmerman; Bryen A. Jordan; Jessica C. Mar (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Women are at increased risk for Alzheimer's disease (AD), but the reason why remains unknown. One hypothesis is that low estrogen levels at menopause increases vulnerability to AD, but this remains unproven. Methods We compared neuronal genes upregulated by estrogen in ovariectomized female rhesus macaques with a database of >17,000 diverse gene sets and applied a rare variant burden test to exome sequencing data from 1208 female AD patients with the age of onset < 75 years and 2162 female AD controls. Results We found a striking overlap between genes upregulated by estrogen in macaques and genes downregulated in the human postmortem AD brain, and we found that estrogen upregulates the APOE gene and that progesterone acts antagonistically to estrogen genome‐wide. We also found that female patients with AD have excess rare mutations in the early menopause gene MCM8. Discussion We show with genomic data that the menopausal loss of estrogen could underlie the increased risk for AD in women.